The Legal Status of Independent Regulatory Organs and Their Place in the Hungarian State Administration - Kálmán, János (Public Governance, Administration and Finances Law Review, 2023)
Independent regulatory organs as a type of administrative body were included among the central state administrative bodies upon the entry into force of the Fundamental Law of Hungary. The key feature of independent regulatory organs is that they also have the power to legislate within the framework of the regulatory authority’s activity; in other words, they can intervene in the relations of their administered sector through the creation of generally binding rules of conduct, which are enforced through the official activities falling within their scope of duties and powers. The characteristics of the legal status of independent regulatory organs and the components of their independence are therefore of particular importance in the system of public administration. The content and strength of their independence are not identical but are adapted to the professional content and EU and constitutional requirements of the specialised area of administration for which the Fundamental Law authorises the National Assembly to establish these bodies.